Repeated reconstruction in patients with atherosclerosis obliterans with long-term complications - V. A. Gubka (Patologìâ)
In the clinic of hospital surgery over the past 10 years 844 reconstructive operations were performed. Of these, a variety of long-term complications were developed in 231 (27,3%) patients. The most frequently identified complications were thrombosis – 50,5%, anastomotic aneurysms – 27,2% and late suppuration - in 22,3 % of patients. All patients were examined: USDG, angiography, fistulography. In patients with thrombosis thrombectomy or replacement of the prosthesis with reconstruction of the bifurcation of the distal anastomosis were performed, with aneurysm - excision of the aneurysm and reconstruction of distal anastomosis, in patients with suppuration - the elimination of the purulent center and, if possible, extraanatomic bypass surgery. Positive results were obtained in 64,4% of patients.